Changing territorialities in the Argentine Andes: lithium mining at Salar de Olaroz-Cauchari and Salinas Grandes - Dorn, Felix Malte (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
In the context of climate change, electro-mobility has become a symbol of hope to reduce the emissions of the growing transport sector. At the same time, it has also renewed interest in strategic resources utilized in battery production, such as lithium. In the areas of extraction, reactions to lithium mining range from hope for paid work and increased in-come to resistance and conflict. Based on extensive ethnographic fieldwork stays realized between February 2018 and August 2019, this article associates the opposed reactions to lithium mining in the communities of the drainage basins of Salar de Olaroz-Cauchari and Salinas Grandes-Guayatayoc with divergent territorialities. In doing so, historically different strategies – resistance and negotiation – of dealing with overlapping territorialities can be identified. Based on a reciprocal relationship, different strategies and divergent territorialities are mutually dependent. In the two case studies, the new territoriality related to the global market implies diverging socio-spatial consequences with different risks. Using the example of lithium mining, it can thus be shown that the sustainability transition continues to be based on social-ecological inequalities and global asymmetries of power.